The use of petrophysical data in mineral exploration: A perspective. Issue 1 (1st December 2018) - Dentith, Mike; Adams, Cameron; Bourne, Barry
Abstract : Using geophysical data for recognising targets for testing and accurately mapping the geology are equally dependent on petrophysics, which constitutes a link between the geologist's largely mineralogical 'view' of the Earth and the geophysicist's physics-based 'view'. The availability of portable petrophysical instruments and spectral scanners allow co-located multiple geochemical, mineralogical and physical property measurements and allow larger volumes of petrophysical property data to be collected, and in a better geological context, than has been possible in the past. Many rock physical properties are heterogeneous and a large number of data is required. Accurate interpretation of the data requires analysis of the data as populations and in the context of all of lithology, alteration, stratigraphy and spatial location. This requires close integration of the petrophysical data with the geochemical and mineralogical data. A recommended interpretation workflow will be demonstrated using two examples: ultramafic rocks from greenstone terrains and carbonate successions hosting base-metal mineralisation.